2004
DOI: 10.3168/jds.s0022-0302(04)73468-2
|View full text |Cite
|
Sign up to set email alerts
|

Extended Ceftiofur Therapy for Treatment of Experimentally-Induced Streptococcus uberisMastitis in Lactating Dairy Cattle

Abstract: Streptococcus uberis is an important cause of mastitis in dairy cows throughout the world, particularly during the dry period, the period around calving, and during early lactation. Strategies for controlling Strep. uberis mastitis are poorly defined and are currently inadequate. Objectives of the present study were to evaluate efficacy of ceftiofur, a new broad-spectrum cephalosporin antibiotic, for treatment of experimentally induced Strep. uberis intramammary infections (IMI) in lactating dairy cows during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 14 publications
4
50
1
7
Order By: Relevance
“…In addition, SCC was determined (by Z1 Coulter counter, Coulter Electronics, Luton, UK) in three sequential aseptic milk samples taken from each of the four mammary quarters once a week before the experiment was begun, as described previously (Younis et al 2003, Leitner et al 2006. Bacterial examination was performed according to the International Dairy Federation procedures using accepted standards for bacteriological typing (Oliver et al 2004). …”
Section: Animals and Milk Samplesmentioning
confidence: 99%
“…In addition, SCC was determined (by Z1 Coulter counter, Coulter Electronics, Luton, UK) in three sequential aseptic milk samples taken from each of the four mammary quarters once a week before the experiment was begun, as described previously (Younis et al 2003, Leitner et al 2006. Bacterial examination was performed according to the International Dairy Federation procedures using accepted standards for bacteriological typing (Oliver et al 2004). …”
Section: Animals and Milk Samplesmentioning
confidence: 99%
“…Similar to S. marcescens infections, IMI's caused by S. uberis are predominantly subclinical and can persist for long periods of time in a chronic state [21,22,40]. Currently recommended antibiotic therapy in the USA for S. uberis IMI remains sub-optimal as two-day treatment with pirlimycin was recently reported to eliminate only 58% of infections [38].…”
Section: Introductionmentioning
confidence: 99%
“…Oliver et al [88,90] investigated the effect of time using the third-generation cephalosporin ceftiofur to treat S. uberis mastitis for two, five, and eight days. Bacterial cure rates for naturally-occurring, subclinical cases were to 17, 56, and 67%, resp.…”
Section: Therapymentioning
confidence: 99%
“…Several studies demonstrated that the extension of the therapy is advantageous [85,[87][88][89][90]. Oliver et al [88,90] investigated the effect of time using the third-generation cephalosporin ceftiofur to treat S. uberis mastitis for two, five, and eight days.…”
Section: Therapymentioning
confidence: 99%